Risques littoraux et préparation à la gestion de crise : quelles synergies entre l’état et les collectivités territoriales ? Exemple de la gestion des pollutions maritimes - Sophie Bahé (VertigO)
According to a very high density of traffic, the French coastline has suffered from maritime pollution since the 1960’s (Torrey Canyon, Amoco Cadiz, Erika, Ievoli Sun, Prestige, etc.). The risk of maritime pollution is changing nature and complexity due to increase and diversification of good transported by sea. In France, until a recent period, only the State staff was prepared to face the management of these events through contingency plans (POLMAR Mer plan for response at sea and POLMAR Terre plan for response on shoreline). The Civil Safety Modernisation Law of 13th August 2004 has restructured the civil safety trough a new ORSEC system which includes the creation of a local contingency plan in order to help local authorities to be prepared. In the same time, local and regional councils’ duties have reinforced by the decentralization and the European Union has been more and more involved in maritime safety. That’s why it is essential to promote a coherent and complementary approach between all these stakeholders. The “Infra POLMAR” process, lead by Vigipol since 2005 on the North coast of Brittany, aims at providing an operational response for all these stakes at local level.